Development of Autoregressive Time Series Model for Prediction of Rainfall and Runofff or Manshara Watershed of Lower Gomati Catchment - Rai, Eno; Sherring, Arpan (Journal of Agricultural Engineering, 2007)
A study was conducted to develop a stochastic time series model for prediction of annual rainfall and runoff in Manshara watershed of lower Gomati catchment. This is one of the sub-watersheds of lower Gomati catchment and has an area of 11.18 kmÂ². The developed model is based on 13 years data from 1991 to 2003. Autoregressive (AR) model of order 0, 1 and 2 proposed by Kottegoda and Horder (1980) were tried. The goodness of fit and adequacy of models were tested by Box-Pierce Portmonteau test, Akaike Information Criterion (AIC) and various statistical characteristics viz., Mean Forecast Error (MFE), Mean Absolute Error (MAE), Mean Relative Error (MRE), Mean Square Error (MSE), Root Mean Square Error (RMSE) and Integral Square Error (ISE). Based on the results, it was concluded that AR (1) model can be effectively used for prediction of rainfall and runoff in Manshara watershed.